HASIL MENULIS KARANGAN SEDERHANA PESERTA DIDIK KELAS X IPA 2 SMAN 1 DRIYOREJO DENGAN METODE CHAIN WRITING - R. Calon, Dorotea (LATERNE, 2017)
This study examines the outcomes of learning the German language writing skills of students of class X IPA 2 SMAN 1 Driyorejo. This title has been selected on the basis problem in learning the German language which has a different structure of writing compared to other languages, such as the use of the article and change the verb that causes learning the German language into something that is not easy for learners, especially in writing skills are the skills most complex when compared with other language skills. Therefore Chain Writing method is used to facilitate students in learning the German language writing skills. The problem of this research is